(untitled) (Journal of the College of Basic Education, 2022)
Targeted research measuring life skills for teachers during the service, and to achieve the goal of search coined researchers null hypothesis the following : " There is no difference statistically significant at the level of significance (0.05) between the average scores teachers of the experimental group who were exposed to the training program, and the average grades teachers in the control group who did not exposed to the training program in the scale of life skills posttest ". The population of the current research of teachers in primary schools of the Directorate of Education in Baghdad Rusafa first academic year (2016 - 2017) m and the number ( 11702 ) teachers rose (1968 ) male and ( 9734 ) parameter , and distributed in the (391) School , by (190 ) School for Boys , and (201) School for Girls . And selected school Mutanabi Boys among the elementary schools of the Directorate of Baghdad Rusafa the first sample in a deliberate , the number of teachers in this school a sample of the experiment (26 ) teachers were divided into two groups : the experimental group (exposed to the training program) (13 ) teachers and the control group ( not exposed to the training program) (13)) teachers. To achieve the goal of research and hypothesis , the researchers prepared two tools : one measure consists of life skills (30) paragraph in his two terms and given the alternatives ( always , often , sometimes , rarely , never) and the weights ( 1,2,3,4,5) respectively , the other , the training program. It was the use of chi square , Pearson correlation coefficient , test Altaúa the (T.test) for two independent samples , test Mann – Whitney. The research found the following results: 1 - that the sample did not have the life skills high , so came the need for the application of the training program is trying to promote the level of life skills forteachers 2 - There is a statistically significant difference at the level of Significance (0.05)among the middle level teacher in the experimental group and the control group in the scale of life skills and in favor of the exper imental group In light of the findings recommended that researchers open training courses for members of the teaching staff in primary education for the use of training programs for the development of life skills , and suggested that researchers conducting a similar study to research the current to identify the impact of the program in other variables , such as the skill to solve the problem , and the skill of decision-making, skill time management, skill psychological and moral thinking and discovery.